2007
DOI: 10.1177/0969733007073697
|View full text |Cite
|
Sign up to set email alerts
|

Moral Obligations of Nurses Based on the ICN, UK, Irish and Polish Codes of Ethics for Nurses

Abstract: A code of professional conduct is a collection of norms appropriate for the nursing profession and should be the point of reference for all decisions made during the care process. Codes of ethics for nurses are formulated by members of national nurses' organizations. These codes can be considered to specify general norms that function in the relevant society, adjusting them to the character of the profession and enriching them with rules signifying the essence of nursing professionalism. The aim of this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…In an American study, Masters of Social Work (MSW) students indicated that they did not feel adequately prepared to handle sexual feelings towards or from a service user (Berkman et al, 2000). Dobrowolska et al (2007) argue that norms are established according to recurring situations, for example by publishing professional misconduct case studies and considering these in the light of relevant clauses of the professional code (see Castledine, 2003).…”
Section: Recognition and Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…In an American study, Masters of Social Work (MSW) students indicated that they did not feel adequately prepared to handle sexual feelings towards or from a service user (Berkman et al, 2000). Dobrowolska et al (2007) argue that norms are established according to recurring situations, for example by publishing professional misconduct case studies and considering these in the light of relevant clauses of the professional code (see Castledine, 2003).…”
Section: Recognition and Reportingmentioning
confidence: 99%
“…Differences in the ways that professional boundaries are drawn and conceived are probably at their most pronounced if one considers the contrasts between collectivist and individualist societies (Rossiter et al, 2002) and societies that have strong religious beliefs (Dobrowolska, 2007).…”
Section: Contextual Issuesmentioning
confidence: 99%
“…"Proximity beckons moral agents to act, and therefore has an impact on moral responsiveness." 13 One of the main criticisms of existing conceptualizations of obligation-based ethics and the principles/codes that arise from them is that they usually present overly simplistic understandings of ethical practice. Subsequently, obligation-based ethics (eg, principle approaching grounded in consequentialism and/or deontology) have been popular within nursing and remain so.…”
Section: Relationships Ethics and Nursing Obligationsmentioning
confidence: 99%
“…The content and function of the codes. These studies dealt with the meaning of the codes in current nursing context (5), their meaning to nurses (27, 63, 64), nurses’ views regarding the development, dissemination and implementation of the codes (28, 65), and nurses’ moral obligations delineated in the codes (66).…”
mentioning
confidence: 99%